2022
DOI: 10.3390/ijerph191911973
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and PTG in French and American Firefighters: A Comparative Study

Abstract: Studies show that experiencing traumatic events can lead to positive psychological change, or posttraumatic growth (PTG). In the hope of promoting PTG, authors have been focusing on identifying the factors that may foster PTG. Despite these attempts, the literature shows inconsistencies, making it difficult to know which variables may be involved in the process of growth. Indeed, authors seem to disagree on the nature of the relationship between PTSD and PTG, time since the event, social support, intrusive rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 114 publications
0
0
0
Order By: Relevance
“…While the Korean study suggests a strong association between burnout and PTSD symptoms, particularly in younger and less experienced firefighters, the US study reveals a pattern of resilience among firefighters during their initial years of service, despite repeated exposure to potentially traumatic events. Taken together, these studies indicate that PTSD and depression symptoms are common among firefighters, particularly during their early years of service, and that exposure to traumatic events on the job is a significant risk factor for the development these mental health conditions (Bezabh et al, 2018;Henson et al, 2022). To prevent and reduce the impact of PTSD and depression among firefighters, it is suggested that preventative interventions should focus on developing resilience, social support, and targeted support for those who have previously experienced trauma or stressful life events.…”
Section: Ptsd Worriesmentioning
confidence: 89%
“…While the Korean study suggests a strong association between burnout and PTSD symptoms, particularly in younger and less experienced firefighters, the US study reveals a pattern of resilience among firefighters during their initial years of service, despite repeated exposure to potentially traumatic events. Taken together, these studies indicate that PTSD and depression symptoms are common among firefighters, particularly during their early years of service, and that exposure to traumatic events on the job is a significant risk factor for the development these mental health conditions (Bezabh et al, 2018;Henson et al, 2022). To prevent and reduce the impact of PTSD and depression among firefighters, it is suggested that preventative interventions should focus on developing resilience, social support, and targeted support for those who have previously experienced trauma or stressful life events.…”
Section: Ptsd Worriesmentioning
confidence: 89%
“…While the Korean study suggests a strong association between burnout and PTSD symptoms, particularly in younger and less experienced firefighters, the US study reveals a pattern of resilience among firefighters during their initial years of service, despite repeated exposure to potentially traumatic events. Taken together, these studies indicate that PTSD and depression symptoms are common among firefighters, particularly during their early years of service, and that exposure to traumatic events on the job is a significant risk factor for the development these mental health conditions (Bezabh et al, 2018;Henson et al, 2022). To prevent and reduce the impact of PTSD and depression among firefighters, it is suggested that preventative interventions should focus on developing resilience, social support, and targeted support for those who have previously experienced trauma or stressful life events.…”
Section: Ptsd Worriesmentioning
confidence: 99%